Evidence of nuclear transport mechanisms in the protozoan parasite Giardia lamblia - Mayol, Gonzalo Federico (2020)
Nuclear-cytoplasmic trafficking of proteins is a highly regulated process that modulates multiple biological processes in eukaryotic cells. In Giardia lamblia, shuttling has been described from the cytoplasm to nuclei of proteins during the biological cell cycle of the parasite. This suggests that a mechanism of nucleocytoplasmic transport is present and functional in G. lamblia. By means of computational biology analyses, we found that there are only two genes for nuclear transport in this parasite, named Importin α and Importin β. When these transporters were overexpressed, both localized close to the nuclear envelope, and no change was observed in trophozoite growth rate. However, during the encystation process, both transporters induced an increase in the number of cysts produced. Importazole and Ivermectin, two known specific inhibitors of importins, separately influenced the encysting process by inducing an arrest in the trophozoite stage that prevents the production of cysts. This effect was more noticeable when Ivermectin, an anti-parasitic drug, was used. Finally, we tested whether the enzyme arginine deiminase, which shuttles from the cytoplasm to the nuclei during encystation, was influenced by these transporters. We found that treatment with each of the inhibitors abrogates arginine deiminase nuclear translocation and favors perinuclear localization. This suggests that Importin α and Importin β are key transporters during the encystation process and are involved, at least, in the transport of arginine deiminase into the nuclei. Considering the effect produced by Ivermectin during growth and encystation, we postulate that this drug could be used to treat giardiasis.